Accurate density measurement of stainless steel weights by hydrostatic weighing system. (January 2019) - Hayu, R.; Sutanto, H.; Ismail, Z.
Highlights: RCM LIPI has built a hydrostatic weighing system. The weight carrier of the system is designed to load four sample weights. Gravitational ratio affects the value of mass correction. The largest uncertainty contribution is the difference of balance indication. The results are in accordance with the required density limit value for E1 class weight. Abstract: A hydrostatic weighing system has been designed and developed to measure the density of stainless steel weight. This system has been designed to load four sample weights with nominal mass 20 g to 1 kg. Distilled water is used as reference liquid in this system. The correction of mass value due to gravitational ratio was significant in nominal mass 500 g and 1 kg. The density measurement results at 20 °C have an expanded uncertainty of 3.6 kg·m −3 for a nominal mass of 20 g and 0.24 kg·m −3 for a nominal mass of 1 kg. The largest component of this uncertainty is due to different balance indication. The results obtained are in accordance with a limit of density value for E1 class weight which is required in OIML R111.